Legislative Smoking Bans for Reducing Exposure to Secondhand Smoke and Smoking Prevalence: Opportunities for Georgians - Steven Coughlin; Jennifer Anderson; Selina Smith (Georgia Southern University, 2015)
Background: Secondhand smoke, which is also referred to as environmental tobacco smoke and passive smoke, is a known human carcinogen. Secondhand smoke also causes disease and premature death in nonsmoking adults and children. Methods: We summarize studies of secondhand smoke in public places before and after smoking bans, as well as studies of cardiovascular and respiratory disease before and after such bans. Results: To protect the public from the harmful effects of secondhand smoke, smoke-free legislation is an effective public health measure. Smoking bans in public places, which have been implemented in many jurisdictions across the U.S. and in other countries, have the potential to influence social norms and reduce smoking behavior. Conclusions: Through legislative smoking bans for reducing secondhand smoke exposure and smoking prevalence, opportunities exist to protect the health of Georgians and other Americans and to reduce health care costs. These opportunities include increasing the comprehensiveness of smoking bans in public places and ensuring adequate funding to quit line services.